ANALYSIS OF THE IMAGE OF KUPANG’S STRAAT ‘A’ - Saudale, Joenel Permana; Lake, Reginaldo Christophori; Rayawulan, Robertus Mas; Jeraman, Pilipus; Lily, Budhi B.; Uak, Alexianus T. M.; Kolawole Opeyemi Morakinyo (International Journal on Livable Space, 2024)
"City image" refers to the perception of a city, shaped by visual experiences, social interactions, and cultural influences. It includes physical elements like architecture and landscapes, as well as intangible factors that define the city's identity and functionality.Aims: This research project aims to explore the relationship between the tangible and intangible aspects of the image of Kupang's Straat "A" neighborhood.Methodology and Results: The research first examines Kevin Lynch's city image principles. It documents the physical elements of Straat "A" using tissue analysis maps, followed by an analysis of both physical and non-physical elements through perceptual and experiential approaches. Finally, the dominant elements of Kupang's Straat "A" urban image are interpreted.Conclusion and Impact: The research identifies three of the five physical elements of city image—paths, districts, and nodes—along with dominant non-physical elements like collective stories, identity, social activities, and user experiences. These findings enhance city image theory and offer valuable insights for urban design, particularly for architects and stakeholders.